Pengaruh Peranan Orang Tua dan Motivasi Belajar Siswa terhadap Hasil Belajar Mata Pelajaran Pai Siswa Kelas VII di SMP Islam Al-Qudwah Cibinong Bogor - Neni Yuningsih; Arman Paramansyah; Yusi Srihartini (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
This research was conducted to answer problems, first, what is the role of parents in learning outcomes. second, what is the student's learning motivation in PAI subjects, Research uses quantitative descriptive, namely the method used to research certain populations and samples, data collection uses research instruments, data analysis is quantitative/statistical, with the aim of testing predetermined hypotheses, based on The results of the analysis show firstly that the influence of the role of parents on student learning outcomes is 0.368 (36.8%). This means that the parental role variable (X1) has a significant and positive effect on the student learning outcome variable (Y). second. The influence of student learning motivation on student learning outcomes is 0.436 (43.6%). This means that the student learning motivation variable (X2) has a significant and positive effect on the student learning outcome variable (Y). Third, the coefficient of determination (R square) is 0.241 or 24.1%. This means that it can be concluded that 24.1% of student learning outcomes are determined by the role of parents and student learning motivation, while the remaining 75.9% is influenced by variance in other variables not explained in this research. Based on these findings, it is recommended that schools should pay more attention to parents by always socializing to encourage parents to continue and increase their attention to the motivation of children's learning activities, both in terms of providing guidance, advice, encouragement, supervision, and equipment for children's learning facilities, as well as fostering a harmonious relationship with their children, so that children will be motivated and can improve their learning outcomes, which in the end will result in satisfactory learning outcomes that meet expectations.